The influence of subsidiary managers on multinational enterprise headquarters’ decisions regarding emerging market subsidiary corporate social responsibility programmes to create local social advantage - Rowley, Colin (University of Pretoria, 2025)
Mini Dissertation (MPhil (International Business))--University of Pretoria, 2024.